2023
DOI: 10.1002/ejhf.3025
|View full text |Cite
|
Sign up to set email alerts
|

Impella and venoarterial extracorporeal membrane oxygenation in cardiogenic shock complicating acute myocardial infarction

Margriet Bogerd,
Sanne ten Berg,
Elma J. Peters
et al.

Abstract: AimsThis research aimed to give contemporary insight into the use of Impella and venoarterial extracorporeal membrane oxygenation (VA‐ECMO) in myocardial infarction‐related cardiogenic shock (AMICS) and into associated outcomes, adverse events, and resource demands.Methods and ResultsThis nationwide observational cohort study describes all AMICS patients treated with Impella(ABIOMED, Danvers, USA) and/or VA‐ECMO in 2020–2021. Impella and/or VA‐ECMO were used in 20% of all AMICS cases(n = 4088). Impella patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Despite today's doctors having access to an extensive array of high-technological heart and lung-supporting devices to acutely support critically ill patients, the mortality among this precarious patient group remains exceedingly high. Here, we discuss the recent large nationwide German database by Bogerd et al 1 which reported that 8% of patients with acute myocardial infarction (AMI) who underwent a percutaneous coronary intervention (n = 256 112) presented with cardiogenic shock (CS) (n = 4088) and that AMI complicated by CS (AMICS) is still associated with a high in-hospital mortality (more than one out of two patients) in line with recent registries 2 and randomized controlled trials. 3 This contemporary real-world experience (2020-2021) is particularly valuable, as opposed to previous studies with similar methodology from the US 4 which evaluated almost 20 years of care, with inherent limitations of major changes introduced in all aspects of care over the study timeline.…”
Section: This Article Refers To 'Impella and Venoarterial Extracorpor...mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite today's doctors having access to an extensive array of high-technological heart and lung-supporting devices to acutely support critically ill patients, the mortality among this precarious patient group remains exceedingly high. Here, we discuss the recent large nationwide German database by Bogerd et al 1 which reported that 8% of patients with acute myocardial infarction (AMI) who underwent a percutaneous coronary intervention (n = 256 112) presented with cardiogenic shock (CS) (n = 4088) and that AMI complicated by CS (AMICS) is still associated with a high in-hospital mortality (more than one out of two patients) in line with recent registries 2 and randomized controlled trials. 3 This contemporary real-world experience (2020-2021) is particularly valuable, as opposed to previous studies with similar methodology from the US 4 which evaluated almost 20 years of care, with inherent limitations of major changes introduced in all aspects of care over the study timeline.…”
Section: This Article Refers To 'Impella and Venoarterial Extracorpor...mentioning
confidence: 99%
“…In this large nationwide study, only few patients were bridged to heart replacement therapies (<10) as it was the case in the IABP-SHOCK II study (33/598 patients received a VAD [5.5% of the whole population] and none HTx) and the ECLS-SHOCK trial (no VAD or HTx reported) signing the absence of consideration of the global patient trajectory in case of lack of recovery (>50% of death causes were secondary to refractory CS in the IABP-SHOCK II and ECLS-SHOCK trials). 1,3,7 The pre-determined endpoint of short-term mortality is subject to debate as in-hospital/30-day mortality is probably too short and insufficient to cover and consider potential benefit/harms of each therapeutic strategy. The use of aMCS is associated with frequent and potentially severe complications responsible for acute consequences, high costs and chronic psychological (depression, post-traumatic stress disorders) and physical sequalae (intensive care unit-associated neuropathy, sarcopenia, infections, altered mental state) that are rarely studied and reported.…”
Section: This Article Refers To 'Impella and Venoarterial Extracorpor...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the Journal, Bogerd and colleagues present data on contemporary use of MCS for AMICS in Germany in 2020-2021. 3 MCS was used in 4088 out of 20 399 patients (20%) with AMICS. The most frequently used device was mAFP and least frequent combination of mAFP and VA-ECMO (ECMELLA).…”
mentioning
confidence: 99%
“…Observational studies like the study by Bogerd et al 3 will still be important in AMICS to demonstrate real-life standard of care, but retrospective analyses of administrative databases are not suited for assessing efficacy. Even trying to identify patients most likely to benefit or being harmed by MCS from large registries with in-depth knowledge of haemodynamic and metabolic status may be problematic.…”
mentioning
confidence: 99%